Opinions of Gen Z Surabaya Regarding the Effectiveness of the Spokes Character Ronald Mcdonald in Communicating McDonalds' Brand Image. - Amadea Daphne Isjwara; Inri Indrayani; Chory Angela Wijayanti (Petra Christian University, 2024)
This research was conducted to determine the opinion of Gen Z in Surabaya regarding the effectiveness of Ronald McDonald's Spokes Character in communicating the McDonald's brand image. McDonalds as a fast-food restaurant uses a mascot to communicate its brand image, namely Ronald McDonald. The elements that determine the effectiveness of spokes character include Relevance to product, Expertise and Nostalgia. To measure the effectiveness of the spokes character, opinions were measured among Gen Z Surabaya, which is the dominant population and is interested in McDonalds. Gen Z Surabaya's opinion will be based on three progressive stages, namely Awareness, Acceptance and Action. So, to find out the opinion of Gen Z Surabaya regarding Ronald McDonald's spokes character, researchers conducted descriptive research with a quantitative approach. The method used was a survey of 100 Gen Z McDonald's Surabaya customers. The results of the research show that the Opinion of Gen Z Surabaya regarding the Effectiveness of Ronald McDonald's Spokes Character in Communicating the McDonalds Brand Image is positive and Expertise as the favourable element.